A Study of Representation and Portrayal of Women in Selected Nigerian Arabic Plays - Rahman, Lawal (DIROSAT: Journal of Education, Social Sciences & Humanities, 2024)
Research has shown that women are not well portrayed and un-equally represented as men in African Literature. This paper investigates how far this claim is true in relation to the Nigerian Arabic plays. The research is analytic and descriptive in nature. The study analyses the representation of women and describes their portrayal in six (6) randomly selected Nigerian Arabic plays namely; Ustadhun Ragma Anfih (A Teacher in Defiance of Him), Fi-Mash-had at-Tilifisyun (At the Television Viewing centre), Al-Dhakhirat(The Relic), Baqaaun Muqaddar (Destined to survive), As-sayyid Al-muhadir (Mr. Lecturer) and Al-Hasad (The Harvest).The result of the analyses of the characterization ,with the aid of ratio and simple percentage, reveals that women are poorly represented in all the selected plays and the examination of the roles assigned to women in the selected texts shows that women are portrayed as illiterate, evil, liars, sex toys and disobedient.This paper recommends that authors of the Nigerian Arabic plays should assign more positive roles to women in their writings to reveal some of the positive roles played by women in the society and equally put more female characters in the characterization.